Impact of nihilistic trend on the style of dramatic stage scenery - Kai Zhang (Trans/Form/Ação)
The purpose of this article is to explore how nihilism, as a philosophical trend of thought, profoundly affects the stage design of modern drama. Nihilism emphasizes the lack of inherent meaning in the world and the absurdity of human existence. Based on this, this article puts forward the argument that nihilism has had a significant impact on the modern drama. Through simplification, abstraction and subversive stage design, the audience is prompted to re-examine the relationship between drama and reality at the visual and psychological levels. The article will explore the concept, generation and artistic expression of nihilism, compare the traditional Western and Chinese theatrical stage set styles, and demonstrate the unique influence of nihilism on theatrical stage sets from the four aspects of stage design, expression techniques, space use and subversion of traditional theatrical forms. Through the analysis of the works of dramatists, such as Pinter, it shows how nihilism is embodied in the specific design of the stage set to support the argument.